INCIDENCE OF CONGENITAL ANOMALIES: A HOSPITAL BASED STUDY - Abbasi, Azizunnisa; Begum, Nazakat; Devi, Bhagwant; Hussain, M.; Waqar, Fareesa (Journal of Ayub Medical College Abbottabad, 1995)
During 18 months' period (January 1994-June 1995), 64 congenitally malformed babies were delivered in Obst/Gyn unit of Women and Children Hospital Abbottabad. Incidence was 2.9%. Neural tube defects were 42 (65.62%), hydrocephalus 16 (25%), cleft lip and cleft palate 3 (4.68%), amelia one (1.56%), polydactyly one (1.56%) & anophthalmia one (1.56%). 13 (20.3%) mothers were primigravidas, 29 (45.31%) were multiparas and 22 (34.37%) were grand multiparas. All of them belonged to poor socio-economic class. 9 were booked and 55 (85.93%) were un booked. There was no history of X-ray exposure, drugs intake, high grade fever or congenitally malformed babies. 4 (6.25%) mothers of babies with neural tube defects were known diabetics.